Procedural Rights and Factual Accuracy - Stewart, Hamish (Legal Theory, 2020)
People have procedural rights because states are under a duty of political morality to provide them with fair procedures for settling disputes about the application of the laws. This obligation flows from the state's duty to treat each person as a free and equal member of the legal order. Yet adherence to procedural rights can impede accuracy in fact-finding, which in turn can result in poor protection for substantive rights. So the state also has a duty to provide a reasonable degree of accuracy in fact-finding. The legal order should therefore strive to improve the accuracy of fact-finding, within the constraints imposed by procedural rights people have. Nevertheless, the duty to provide reasonably accurate procedures is subordinate to the duty to provide procedural rights because the settlement of disputes among free persons must be conducted in a manner that respects their status as free persons.